Comparison of 2 Patient-Reported Outcome Measures in Brachial Plexus Birth Injury: A Systematic Validation Study. - Vuillermin, Carley FRACS; Eisenberg, Katherine; Williams, David; Tartarilla, Ashley B.; Bauer, Andrea; Waters, Peter M.; Vuillermin, Carley (Journal of Bone & Joint Surgery, American Volume, 2022)
Background: Patient-reported outcome (PRO) measures are integral to clinical practice. While new instruments bring updated methodology and delivery methods, they must be compared with existing measures to ensure that they are comparable with currently used instruments and allow ongoing comparison. In this study, we evaluated 2 PRO measures for patients with brachial plexus birth injury (BPBI): the legacy Pediatric Outcomes Data Collection Instrument (PODCI) and the newer Patient-Reported Outcomes Measurement Information System (PROMIS). We hypothesized that the PROMIS and PODCI would be correlated, with high convergent validity, and that PROMIS assessment would have higher discriminant validity and take less time to complete than the PODCI.Methods: A cross-sectional prospective study was undertaken at a tertiary referral center. Subjects (n = 50) completed the PODCI and PROMIS, both as short form (SF) and computer-adaptive testing (CAT) measures, in randomized order. Patient and parent questionnaires were completed according to subject age. Physicians completed upper-extremity (UE) physical function tests. Correlations between PODCI and PROMIS scores were analyzed to determine convergent validity, UE subscores were analyzed relative to physical function scores to assess discriminant validity, and completion times were calculated to determine survey time to completion.Results: High convergent validity was found between the parent-reported PODCI, PROMIS SF, and PROMIS CAT measures. A ceiling effect was found for the PODCI but not for the PROMIS. The PROMIS CAT had better discriminant validity than either the PROMIS SF or PODCI. Patient and parent outcome scores did not highly correlate. Survey time to completion varied by PRO measure and method of delivery.Conclusions: There was high convergent validity between the UE domains of the PROMIS and PODCI, with a lower time to completion for the PROMIS SF. Although results show that the PROMIS CAT may take longer to complete, there are notable benefits to its adoption, including high convergent validity with the PODCI and better discriminant validity than the PODCI and PROMIS SF measures.